(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Today, arming the young generation with modern knowledge and educating them to be the possessors of strong knowledge that can compete with their peers in the world has become an urgent issue of today. The huge opportunities that are being created contribute to the education of the young generation. Special attention to the growing young generation at each educational age indicates that youth education has risen to the level of state policy. Interest in learning, aspiration, enthusiasm, perseverance, ambition, high potential, characteristic of our nation, are qualities that ensure continuity of generations.